Regulatory T Cells in Endemic Burkitt Lymphoma Patients Are Associated with Poor Outcomes: A Prospective, Longitudinal Study. - Emily Parsons; Juliana A Otieno; John Michael Ong'echa; Christina E Nixon; John Vulule; Christian Münz; V Ann Stewart; Ann M Moormann (PLoS ONE)
Deficiencies in Epstein-Barr virus (EBV)-specific T cell immunosurveillance appear to precede the development of endemic Burkitt lymphoma (eBL), a malaria-associated pediatric cancer common in sub-Saharan Africa. However, T cell contributions to eBL disease progression and survival have not been characterized. Our objective was to investigate regulatory and inflammatory T cell responses in eBL patients associated with clinical outcomes. By multi-parameter flow cytometry, we examined peripheral blood mononuclear cells from 38 eBL patients enrolled in a prospective cohort study in Kisumu, Kenya from 2008-2010, and 14 healthy age-matched Kenyan controls. Children diagnosed with eBL were prospectively followed and outcomes categorized as 2-year event-free survivors, cases of relapses, or those who died. At the time of diagnosis, eBL children with higher CD25+Foxp3+ regulatory T (Treg) cell frequencies were less likely to survive than patients with lower Treg frequencies (p = 0·0194). Non-survivors also had higher absolute counts of CD45RA+Foxp3lo naïve and CD45RA-Foxp3hi effector Treg subsets compared to survivors and healthy controls. Once patients went into clinical remission, Treg frequencies remained low in event-free survivors. Patients who relapsed, however, showed elevated Treg frequencies months prior to their adverse event. Neither concurrent peripheral blood EBV load nor malaria infection could explain higher Treg cell frequencies. CD8+ T cell PD-1 expression was elevated in all eBL patients at time of diagnosis, but relapse patients tended to have persistently high PD-1 expression compared to long-term survivors. Non-survivors produced more CD4+ T-cell IL-10 in response to both Epstein-Barr Nuclear Antigen-1 (EBNA-1) (p = 0·026) and the malaria antigen Plasmodium falciparum Schizont Egress Antigen-1 (p = 0·0158) compared to survivors, and were concurrently deficient in (EBNA-1)-specific CD8+ T-cell derived IFN-γ production (p = 0·002). In addition, we identified the presence of Foxp3-IL10+ regulatory Type 1 cells responding to EBNA-1 in contrast to the malaria antigen tested. These novel findings suggest that poor outcomes in eBL patients are associated with a predominantly immuno-regulatory environment. Therefore, Treg frequencies could be a predictive biomarker of disease progression and manipulation of Treg activity has potential as a therapeutic target to improve eBL survival.